1998
DOI: 10.15554/pcij.05011998.68.80
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Design of Link Slabs for Jointless Bridge Decks

Abstract: Maintenance of bridge deck joints is a costly problem. Debris accumulation in the joints can restrain deck expansion, caus ing undesirable forces in the deck and damage to the structure. Water leaking through the joints is a major cause for the deterioration of bridge girder bearings and supporting structures. Therefore, elimination of deck joints at the supports of multispan bridges will reduce the cost of construction and maintenance. This paper presents the results of a test program to investigate the behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
111
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 3 publications
2
111
0
1
Order By: Relevance
“…Adoption of the jointless bridge design concept eliminates the expansion joint at the bridge center, thereby minimizing future maintenance efforts associated with cracked decks. The design of the ECC link slab follows the link slab design guidelines offered by Caner and Zia [1] originally proposed for concrete link slabs. The link slab is designed to be sufficiently flexible (offering no rotational restraint) to permit the spans on both sides of the link slab to behave as simply supported elements.…”
Section: Grove Street Bridgementioning
confidence: 99%
See 3 more Smart Citations
“…Adoption of the jointless bridge design concept eliminates the expansion joint at the bridge center, thereby minimizing future maintenance efforts associated with cracked decks. The design of the ECC link slab follows the link slab design guidelines offered by Caner and Zia [1] originally proposed for concrete link slabs. The link slab is designed to be sufficiently flexible (offering no rotational restraint) to permit the spans on both sides of the link slab to behave as simply supported elements.…”
Section: Grove Street Bridgementioning
confidence: 99%
“…The link slab is designed to undergo strain induced by the moments developed at the span-link slab interface. If the link slab moment of inertia, I ls , and elastic modulus, E, are known, then the constant moment, M ls , developed in the link slab due to the relative rotation, θ, at the link slab ends is given [1]:…”
Section: Grove Street Bridgementioning
confidence: 99%
See 2 more Smart Citations
“…The leaking expansion joints are a major source of deterioration of multi-span bridges in Canada. Expansion joints can be replaced by flexible link slabs made with ECC forming a joint-free multi-span bridge and hence, solving the problem of premature deterioration [23,24]. Research studies showed significant enhancement of ductility and crack width control in ECC link slabs confirming that the use of ECC can be effective in extending the service life of bridge deck systems.…”
Section: Introductionmentioning
confidence: 99%